(untitled) (Historia, 2021)
During the so-called Zulu Rebellion of 1906 a critical stage was reached when the colonial forces were extended to the limit when fresh rebel forces reinforced those active under Bhambatha and other leaders in the Nkandla district of Zululand. The combined forces moved to the Thukela, prepared to cross into Natal, and then turned back and moved eastward. Their exact objective is not known, but southeastern Zululand was in ferment and rumours of an uprising instigated by the former Zulu king Dinuzulu were rife. Was the rebel army going to raise or support it? In any case, the defeat of the army at the battle of Mome on 10 June destroyed rebel prospects. This article examines these hitherto neglected aspects of the rebellion, using fresh sources, and radically reinterprets the narrative of events. Tydens die sogenaamde Zulu Rebellie van 1906 is ’n kritiese fase bereik waartydens die koloniale magte onder groot druk was toe vars rebelle magte, die onder die bevel van Bhambatha en ander leiers, in die Nkandla distrik van Zululand versterk het. Die gekombineerde magte het suid na die Thukela beweeg voordat hul terug gedraai en oos beweeg het. Die presiese doel was nie bekend nie maar die suiooste van Zululand was in rep en roer en gerugte oor ’n opstand aangeblaas deur die voormalige Zulu Koning Dinizulu het die rondte gedoen. Iedergeval, die nederlaag van die Zulu mag op 10 Junie by Mome het al hoop van die rebelle vernietig. In die artikel word tot dusver afgeskeepte aspekte van die rebellie aan die hand van nuwe bronne ondersoek.